2012
DOI: 10.1111/j.1538-7836.2012.04739.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic clinical prediction rules to identify a low‐risk pulmonary embolism: a systematic review and meta‐analysis

Abstract: To cite this article: Squizzato A, Donadini MP, Galli L, Dentali F, Aujesky D, Ageno W. Prognostic clinical prediction rules to identify a low-risk pulmonary embolism: a systematic review and meta-analysis. J Thromb Haemost 2012; 10: 1276-90.Summary. Background: Prognostic assessment is important for the management of patients with a pulmonary embolism (PE). A number of clinical prediction rules (CPRs) have been proposed for stratifying PE mortality risk. The aim of this systematic review was to assess the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
38
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 52 publications
(151 reference statements)
2
38
0
2
Order By: Relevance
“…A recent large meta-analysis confirmed the role of the PESI score in the identification of PE patients at a low risk of mortality, 11 and patients with a PESI score of I-II were included in a randomized controlled trial that confirmed the safety and efficacy of home treatment of acute PE. 17 Unfortunately, the PESI score categorizes patients into 5 risk classes and it is not easy to compute.…”
mentioning
confidence: 99%
“…A recent large meta-analysis confirmed the role of the PESI score in the identification of PE patients at a low risk of mortality, 11 and patients with a PESI score of I-II were included in a randomized controlled trial that confirmed the safety and efficacy of home treatment of acute PE. 17 Unfortunately, the PESI score categorizes patients into 5 risk classes and it is not easy to compute.…”
mentioning
confidence: 99%
“…Risk stratification tools for emergency department (ED) patients with acute pulmonary embolism (PE) can be used to identify patients at low risk for complications (1). Many of these low-risk patients are eligible for outpatient management (2,3).…”
mentioning
confidence: 99%
“…While DVT has been treated as an outpatient for many years, recently developed risk stratification tools have been validated to select patients with PE who have a low risk of shortterm complications. [1][2][3][4][5][6][7] In particular, the Hestia criteria identifies a subgroup of PE patients who have a 1.0% mortality rate as outpatients over 3 months and a low rate of short-term complications requiring rehospitalization. 8 In this article, we assumed that many patients with DVT have undiagnosed PE and therefore must undergo the same risk stratification as patients with documented PE.…”
mentioning
confidence: 99%